Analysis of Iran's Reasons for Normalizing Diplomatic Relations with Saudi Arabia in 2023 - Aprillia, Ana; Haryo Prasodjo (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2023)
Relations between Saudi Arabia and Iran, which have been heating up in recent years, have finally come to light. The normalization of relations between the two countries cannot be separated from the assistance of China, which is a third party in the process of improving relations between the two. Both began to improve relations with each other by opening diplomatic relations. This study aims to find out the reasons behind Iran opening its diplomatic relations with Saudi Arabia. The study used a qualitative approach with library research data collection techniques via Google Scholar and Publish and Perish platforms. The author finds that there are several reasons for Iran to reopen its diplomatic relations with Arab countries: (1) international pressure such as the US’s economic sanctions, (2) economic interests by opening embassies in both countries, (3) stability following the normalization of the relations, especially on Sunni-Shia issues and establishing the Middle East’s hegemony, (4) the role of China, (5) the tendency of Saudi Arabia to China instead of the USA, and (6) the failure of Saudi Arabia in the Yemen war.